Assessment of melanogenesis in a pigmented human tissue-cultured skin equivalent - Nadja Nicole Zoller; Matthias Hofmann; Manuel Butting; Igor Hrgovic; Jürgen Bereiter-Hahn; August Bernd; Roland Kaufmann; Stefan Kippenberger; Eva Valesky (Wolters Kluwer Medknow Publications, 2019)
Background: Organotypic tissue-cultured skin equivalents are used for a broad range of applications either as possible substitute for animal tests or for transplantation in patient-centered care. Aims: In this study, we implemented melanocytes in a tissue-cultured full-thickness skin equivalent, consisting of epidermis and dermis. The versatility of this skin-like model with respect to pigmentation and morphological criteria was tested. Materials and Methods: Pigmented skin equivalents were morphologically characterized, and melanogenesis was evaluated after treatment with kojic acid - a tyrosinase inhibitor and forskolin - a well-known activator of the cyclic adenosine 3,5-monophosphate pathway. Pigmentation was measured either by determination of the extinction at 400 nm after melanin extraction with KOH correlated to a melanin standard curve or by reflectance colorimetric analysis, monitoring reflectance of 660 nm and 880 nm emitting diodes. Results: The morphological analysis revealed characteristic epidermal stratification with melanocytes located at the basal layer. Stimulation with forskolin increased the pigmentation, whereas treatment with kojic acid caused bleaching. Conclusion: The present study demonstrates that the herein-introduced organotypic tissue-cultured skin equivalent is comparable to the normal human skin and its versatility in tests regarding skin pigmentation. Therefore, this model might help understand diseases with dysfunctional pigmentation such as melasma, vitiligo, and postinflammatory hyperpigmentation.